Selective heavy metal receptor functional phthalocyanines bearing thiophenes: Synthesis, characterization, spectroscopy and electrochemistry - KOCA, ATIF (ELSEVIER SCI LTD, 2008)
Soft metal ion receptor 2,9,16,23-tetrakis-6-(-thiophene-2-carboxylate)-hexylthio-phthlocyaninato zinc(II) and cobalt(II) complexes derived from 6-(3,4-dicyanophenylthio) hexyl thiophene-2-carboxyl ate have been prepared as an isomeric mixture via cyclotetramerization reactions. The complexes have been fully characterized by elemental analysis, FTIR, H-1 and C-13 NMR, MS (ESI and MALDI-TOF) and by UV-vis spectral data. Soft metal ion binding ability of the complexes with Ag-I, Pd-II, Hg-II and Cd-II has been evaluated by UV-vis spectroscopic titration technique. Cyclic and differential pulse voltammetries show that while Zn(II)Pc gives up to two ligand-based reduction and one ligand-based oxidation processes having diffusion-controlled reversible electron transfer properties, Co(II)Pc represents one ligand-based and one metal-based oxidation and one metal-based and one ligand-based reduction processes having diffusion-controlled reversible electron transfer characters. Assignments of the redox couples of Co(II)Pc are confirmed by spectroelectrochemical measurements. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; zinc; cobalt; silver; palladium; ion receptor; MALDI-TOF; Electrochemistry; spectroelectrochemistry; FLUORESCENCE-SPECTRA; METALLOPHTHALOCYANINES; COMPLEXATION; BEHAVIOR